La mortalite des veaux dans le troupeau sedentaire du nord Cote d'Ivoire - Camus, E. (1980)
Calf mortality of a breeding stock was investigated. Causes of calf mortality including trypanosomiasis, coccidiosis, strongyloidosis, colibacillosis and ascaridiosis during the dry season are discussed.